2021
DOI: 10.3389/fcvm.2021.671191
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Biomarkers for Congenital Heart Disease Based on Maternal Amniotic Fluid Metabolomics

Abstract: Congenital heart disease (CHD) is the most common birth defect. The prenatal diagnosis of fetal CHD is completely dependent on ultrasound testing, but only ~40% of CHD can be detected. The purpose of this study is to find good biomarkers in amniotic fluid (AF) to detect CHD in the second trimester, so as to better manage this group of people and reduce the harm of CHD to the fetus. Metabolites analysis were performed in two separate sets. The discovery set consisted of 18 CHD fetal maternal AF samples and 35 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…However, these studies used infant or childhood serum samples as material to explore the relationship between metabolites and CHD, and it is relatively rare to study the occurrence of CHD through biological samples obtained from pregnant mothers. Previous studies reported that maternal serum [ 17 ], urine [ 18 , 19 ], and amniotic fluid (AF) [ 20 ] were used to detect metabolites by [ 1 ] H NMR or GC–MS technology. However, these methods for detecting metabolites are more limited than those detected by UHPLC‒MS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies used infant or childhood serum samples as material to explore the relationship between metabolites and CHD, and it is relatively rare to study the occurrence of CHD through biological samples obtained from pregnant mothers. Previous studies reported that maternal serum [ 17 ], urine [ 18 , 19 ], and amniotic fluid (AF) [ 20 ] were used to detect metabolites by [ 1 ] H NMR or GC–MS technology. However, these methods for detecting metabolites are more limited than those detected by UHPLC‒MS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used biological samples such as maternal serum [ 17 ], urine [ 18 , 19 ], and amniotic fluid (AF) [ 20 ] to detect metabolites for exploring biomarkers of congenital heart disease. However, the types of detectable metabolites are limited.…”
Section: Introductionmentioning
confidence: 99%
“…A further study used an untargeted approach to explore whether mid-pregnancy urinary metabolites could accurately discriminate CHD cases from the controls (N = 70 CHD cases and 70 controls) and found that two principal components separated the cases and the controls, with 4-hydroxybenzeneacetic acid, 5-trimethylsilyloxy-n-valeric acid, hydracrylic acid and propanedioic acid driving their differences [ 11 ]. Finally, a study in a Chinese population of metabolomic analyses using maternal amniotic fluid (N = 71 CHD cases) found that two metabolites (uric acid and proline) had higher concentrations in CHD affected pregnancies [ 12 ]. In summary, to date there have been few pregnancy metabolomic studies exploring the potential molecular causal mechanisms of CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Replication of these results are warranted. A recent retrospective study in a Chinese population performed metabolomic analyses using maternal amniotic fluid and found that two metabolites (uric acid and proline) were elevated in CHD affected pregnancies 12 . In summary, there have been studies uncovering potentially important biological pathways associated with offspring CHDs.…”
Section: Introductionmentioning
confidence: 99%